تجاوب القمح الطري (Bread wheat) مع التغذية البوتاسية: بعض معايير النمو، الإنتاجية وكفاءتها - علوش غياث; عمران بثينة (Latakia University Journal -Biological Sciences Series, 2018)
أجريت تجربة أصص في بيت بلاستيكي في جامعة تشرين 2016-2017، زرعت بالقمح الطري (صنف شام 6) لدراسة تجاوب القمح مع التسميد بمعدلات متزايدة من البوتاسيوم (K0=0, K1=25, K2=50, K3=75, K4=100, K5=150) مغ K/كغ تربة. أدت الزيادة في معدلات التسميد البوتاسي إلى زيادة معنوية في عدد الإشطاءات الكلية، الإشطاءات المنتجة منها على حساب الإشطاءات غير المنتجة، وكان هنالك زيادة ظاهرية في عدد الحبوب في سنابل السوق الرئيسة حيث تفوقت معاملة المستوى الأول (K1= 25 mg K/kg) من التسميد البوتاسي لسنابل الإشطاء في عدد الحبوب مقارنة بمعاملة الشاهد K0، كما وسجلت ذات المعاملة K1 أفضل وزن للحبوب في سنابل السوق الرئيسة والإشطاءات. ازدادت الإنتاجية من الغلة الحبية مع زيادة التسميد البوتاسي بشكل ظاهري حيث سجلت معاملة التسميد بـ ( 150مغ K/كغ تربة) أفضل غلة حبية وصلت إلى 13933كغ/هـ، والتي تعادل زيادة في الإنتاج بمعدل 18 % مقارنةً بمعاملة الشاهد K0. وبينت حسابات الكفاءة الزراعية أعلى قيمة (حوالي 13 كغ حبوب/كغ سماد بوتاسي) عند المستوى الأول للإضافة (K1)، ومن ثم انخفضت تدريجياً مع زيادة معدلات التسميد البوتاسي لتبلغ حوالي 6 كغ حبوب/كغ سماد بوتاسي في المعاملتين K4 و K5 ( 100و 150 مغ K/كغ). A pot experiment was conducted in a green house at Tishreen University in which bread wheat (cv. Sham 6) was grown at different levels of potassium nutrition (K0=0, K1=25, K2=50, K3=75, K4=100, K5=150) mg k/kg soil. The increase in potassium fertilization rates led to a significant increase in the number of total tillers and fertile tillers on the expense of non-fertile tillers. This was accompanied with no significant increase in number of main stems spikes grains, while the tillers spikes of the first level of potassium application (K1) was higher significantly compared to control treatment (K0). The same treatment (K1) gave the best weight of grain on the main stems spikes and tillers. The productivity of grain yield increased (but non-significantly) with increasing the level of potassium fertilization. The highest yield value was obtained in K5 treatment which was 13933 kg /ha. This productivity constitutes a rate of increase 18% compared to the control treatment (K0). The calculation of Agronomic Efficiency (AE) showed a high value of (about 13 kg seeds/kg of K fertilizer added) in the K1 treatment, and thereafter, AE gradually decreased with potassium fertilization to reach about 6 kg grain/kg K fertilizer for K4 and K5 treatments (100 and 150 mg K/kg).